Discriminant Analysis Consumer Behavior in Selecting Online Health Service Applications (Telemedicine) (Study of Mathematics and Natural Sciences Faculticity Brawijaya University Bachelor Student) - Afiz, Athifah Fauzia (Journal of Applied Statistics and Data Science, 2026)
The research was conducted to examine the consumer behavior characteristics, particularly among undergraduate students of the Faculty of Mathematics and Natural Sciences (FMIPA) at Universitas Brawijaya, in selecting online healthcare service applications (telemedicine) using quadratic discriminant analysis. The data used was primary data, collected through quota sampling technique via a survey by distributing questionnaires to 100 respondents. The dependent variable in this study was the selection of applications, divided into Halodoc, Alodokter, and KlikDokter, with the independent variables being trust, ease of use, and price. The analysis was applied to obtain the classification function, classification results, and the strongest discriminating variable. The analysis results showed that the strongest discriminating variable in the formed discriminant function was price, with the largest standardized coefficient among trust and ease of use. The classification accuracy obtained was 58%.